ER calcium depletion as a key driver for impaired ER-to-mitochondria calcium transfer and mitochondrial dysfunction in Wolfram syndrome - Mailis Liiv; Annika Vaarmann; Dzhamilja Safiulina; Vinay Choubey; Ruby Gupta; Malle Kuum; Lucia Janickova; Zuzana Hodurova; Michal Cagalinec; Akbar Zeb; Miriam A. Hickey; Yi-Long Huang; et al. (Nature Communications, 2024)
Abstract Wolfram syndrome is a rare genetic disease caused by mutations in the WFS1 or CISD2 gene. A primary defect in Wolfram syndrome involves poor ER Ca2+ handling, but how this disturbance leads to the disease is not known. The current study, performed in primary neurons, the most affected and disease-relevant cells, involving both Wolfram syndrome genes, explains how the disturbed ER Ca2+ handling compromises mitochondrial function and affects neuronal health. Loss of ER Ca2+ content and impaired ER-mitochondrial contact sites in the WFS1- or CISD2-deficient neurons is associated with lower IP3R-mediated Ca2+ transfer from ER to mitochondria and decreased mitochondrial Ca2+ uptake. In turn, reduced mitochondrial Ca2+ content inhibits mitochondrial ATP production leading to an increased NADH/NAD+ ratio. The resulting bioenergetic deficit and reductive stress compromise the health of the neurons. Our work also identifies pharmacological targets and compounds that restore Ca2+ homeostasis, enhance mitochondrial function and improve neuronal health.